A look at random access for machine‐type communications in 5th generation cellular networks. Issue 1 (18th September 2017) - Grassi, Alessandro; Piro, Giuseppe; Boggia, Gennaro
Abstract : Machine‐type communications represent a major challenge for the upcoming 5th generation (5G) technology. Future cellular systems, in fact, will be in charge of supporting a huge number of devices generating sporadic small packets at random times. In this context, the random access channel (RACH) protocol is generally used to initiate the communication sessions, aimed at delivering this kind of traffic. But, occasional peaks of requests, generated when many devices react to the same event, may severely degrade network performance (ie, by increasing the collision probability). This letter investigates, through computer simulations, the performance of well‐known procedures for the RACH, designed for the current 4th generation technology and the upcoming 5G system in challenging scenarios never seen before. Specifically, the evaluation targets access peaks caused by emergency situations, including every phase of the protocol from the initial contention to the transmission of the application payload. Obtained results highlight pros and cons of available solutions, while showing challenging issues that should be carefully addressed in future research activities.